Efek Strategic Experiental Marketing (SEMs) dan Implementasinya melalui Key Experiental Providers (ExPROs) terhadap Loyalitas pada Lion Air dan Mandala Air Lines - Handayani, Sri (Jurnal Ekonomi : Journal of Economic, 2010)
Experiential marketing, an approach to create emotional connection with customers through careful planning of tangible and intangible service elements. With ever-increasing competition, service pro-viders seek to develop loyalty by aggressively designing, continuously innovating, and managing their customer experiences. This research empirically investigates and explores the influence bet-ween different service elements designed to create enhanced experience toward on Lion Air and Mandala Air Lines customer loyalty. The secondary purpose of this research is aimed to know how much difference mean of cusomer’s  loyalty between Lion Air and Mandala Air Lines. The sample was taken by clustered sampling method and were analyzed by using regression analysis and mann-whitney U  test. The result of the study proved that there was a simultaneous influence among Sense, Feel, Think, Act, Relate toward Loyalty on Lion Air dan Mandala Airlines passenger. Partially, only Act which had significant influence toward loyalty on Lion Air, and only Relate which had significant influence toward loyalty on Mandala Airlines. In summary, the authors conclude there is no significant difference loyalty between Lion Air and Mandala Airlines . Keywords: Experiential Marketing, Sense, Feel